Anesthetic management in progressive familial intrahepatic cholestasis type i (Byler Disease) - Demirel, Ismail; Bolat, Esef; Altun, Aysun Yildiz; Atici, Erkan; Tartar, Tugay (Anestezi Dergisi, 2018)
Progressive familial intrahepatic cholestasis (PFIC) or Byler disease is one of the most common forms of intrahepatic cholestasis of metabolic and genetic origin. It's an autosomal recessive disease and appears in the first 6 months of life with intrahepatic cholestasis and progressive fibrosis resulting with cirrhosis. Patients usually die because of hepatic deficiency before adolescant period. In this study we would like to report about an eight year old girl diagnosed with Byler disease since 1,5 year of age planned for laparoscopic cholecystectomy due to calculous cholecystitis under general anasthesia. This case report describes the anesthetic features of a patient with Byler's disease in which anesthetic agents with no or minimal hepatotoxic effect should be used to avoid deterioration of liver function. © 2018 Anestezi Dergisi. All rights reserved.
Keywords: Anesthesia management; Byler disease; Laparoscopic cholecystectomy